The impact of behavioral economics on stimulating individual consumption levels of government services: A case study of the General Directorate of Residency and Foreigners Affairs services in Dubai (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aims to explore the impact of behavioral economics—through the tool of behavioral nudging and behavioral insights—on increasing the consumption of digital services at the General Directorate of Residency and Foreigners Affairs (GDRFA) in Dubai. It analyzes the influence of several factors, including enhancing user experience, providing guidance and support, promoting digital awareness and literacy, offering incentives and rewards, and fostering interaction and social engagement. The significance of this study stems from the urgent need to enhance the use of digital services within government institutions to ensure the delivery of efficient, high-quality services to users. The study employs a mixed-methods approach that combines both quantitative and qualitative methodologies to achieve its objectives. Accordingly, it utilizes a questionnaire and purposive in-depth interviews as its main data collection tools. The sample included 150 users of digital services at GDRFA Dubai, in addition to 10 leaders, managers, and department heads who were selected for interviews. The study reached several findings, most notably that the vast majority of survey participants affirmed the importance of behavioral nudging tools in improving user experience, directing guidance and support for digital service use, enhancing digital awareness and literacy, and that incentives and rewards effectively encourage greater use of digital services. Participants also indicated that interaction and social communication strengthen digital service utilization. These findings were further reinforced by the interviewees, who particularly emphasized improving user experience, ensuring continuous technical support, implementing digital awareness and literacy programs, and offering incentives and rewards—along with highlighting the importance of positive engagement on social media platforms as a behavioral nudge toward digital service adoption. In conclusion, the study presents a set of forward-looking recommendations and policy enhancers aimed at achieving the desired objectives of stimulating individual consumption of government digital services.
Keywords: Nudging; Behavioral Insights; Digital Literacy; Digital Service Consumption